Detection of an explosive simulant via electrical impedance spectroscopy utilizing the UiO-66-NH2 metal–organic framework. Issue 43 (20th October 2016) - Peterson, G. W.; McEntee, M.; Harris, C. R.; Klevitch, A. D.; Fountain, A. W.; Soliz, J. R.; Balboa, A.; Hauser, A. J.
Abstract : Electrical impedance spectroscopy, in conjunction with the metal–organic framework (MOF) UiO-66-NH2, is used to detect trace levels of the explosive simulant 2, 6-dinitrotoluene. Abstract : Electrical impedance spectroscopy, in conjunction with the metal–organic framework (MOF) UiO-66-NH2, is used to detect trace levels of the explosive simulant 2, 6-dinitrotoluene. The combination of porosity and functionality of the MOF provides an effective dielectric structure, resulting in changes of impedance magnitude and phase angle. The promising data indicate that MOFs may be used in low-cost, robust explosive detection devices.